Contralateral prophylactic mastectomy: current perspectives - Yao K; Sisco M; Bedrosian I (Dove Medical Press, 2016)
Katharine Yao,1 Mark Sisco,2 Isabelle Bedrosian3 1Division of Surgical Oncology, Department of Surgery, 2Division of Plastic Surgery, Department of Surgery, NorthShore University HealthSystem, Evanston, IL, 3Department of Surgery, MD Anderson Cancer Center, Houston, TX, USA Abstract: There has been an increasing trend in the use of contralateral prophylactic mastectomy (CPM) in the United States among women diagnosed with unilateral breast cancer, particularly young women. Approximately one-third of women ,40 years old are undergoing CPM in the US. Most studies have shown that the CPM trend is mainly patient-driven, which reflects a changing environment for newly diagnosed breast cancer patients. The most common reason that women choose CPM is based on misperceptions about CPM’s effect on survival and overestimation of their contralateral breast cancer (CBC) risk. No prospective studies have shown survival benefit to CPM, and the CBC rate for most women is low at 10 years. Fear of recurrence is also a big driver of CPM decisions. Nonetheless, studies have shown that women are mostly satisfied with undergoing CPM, but complications and subsequent surgeries with reconstruction have been associated with dissatisfaction with CPM. Studies on surgeon’s perspectives on CPM are sparse but show that the most common reasons surgeons discuss CPM with patients is because of a suspicious family history or for a patient who is a confirmed BRCA mutation carrier. Studies on the cost–effectiveness of CPM have been conflicting and are highly dependent on patient’s quality of life after CPM. Most recent guidelines for CPM are contradictory. Future areas of research include the development of interventions to better inform patients about CPM, modification of the guidelines to form a more consistent statement, longer term studies on CBC risk and CPM’s effect on survival, and prospective studies that track the psychosocial effects of CPM on body image and sexuality. Keywords: contralateral breast cancer, surgical decision making